Sistem Digitalisasi di Era Revolusi 5.0 - Lena Elfianty; Jhoanne Fredricka; Achmad Fikri Sallaby; Nofi Qurniati; Juju Jumadi; Annisa Putri Pratiwi (Jurnal Dehasen Untuk Negeri, 2022)
This community service activity in the form of socializing the digitalization system in the 5.0 revolution era aims to help students at SMA Negeri 3 Seluma in getting information about technological advances related to digitalization in the 5.0 revolution era. The subjects in this service activity are students of SMA Negeri 3 Seluma. This socialization process is carried out by providing information about artificial intelligence that pays attention to the human side and will transform millions of data collected through the internet in all areas of life. The results of this community service activity are so that students can be better prepared to face the era of revolution 5.0 in Indonesia by utilizing existing Human Resources (HR) because domestic human resources are no less qualified than foreign human resources, it is also expected that with the 5.0 Revolution This can develop human resources in Indonesia. The conclusion of this community service activity at SMA Negeri 3 Seluma is that the younger generation of students at SMA Negeri 3 Seluma Bengkulu Selatan have creative and inspiring behavior, tend to build their learning patterns with strong interpersonal skills. Young generations who are creative, innovative and productive, from an early age need to be enriched with soft skills as contained in the 5.0 revolution. Of course, this plenary ability is expected to succeed in winning the competition in the disruptive era and the world without borders.